Teacher educators' and students' perspectives in transitioning from conventional to online teaching and learning - Johari, Marlizayati; Omar Ali, Aliamat; Musa, Juraidah; Zakir, Nordiana; Shahrill, Masitah (LPMPP Universitas Negeri Yogyakarta, 2024)
The purpose of this paper is to investigate the impact of COVID-19 pandemic on the sudden transition of teaching and learning from the perspectives of the teacher educators and students of an education graduate faculty in one of the universities in Brunei Darussalam. During the first COVID-19 outbreak in the country, higher education institutions shifted the conventional teaching and learning approach from mostly face-to-face to fully online teaching and learning. The online questionnaires were distributed to the teaching staff and students via email and the response rate of the online questionnaires for teacher educators and students was 88% and 57.6% respectively. Descriptive statistics was used to analyse the data where frequency and percentage were then utilised to describe the patterns of the responses. It was found that half of the teacher educators and students perceived there were more interactions through online teaching activities between the teaching staff and their students. However, both staff and students mentioned that their physical and mental wellbeing were also affected due to the sudden transition to online teaching and learning.